A Master's Degree - McCarter, Margaret Hill, 1860-1938 (Salt Lake City, UT : Project Gutenberg, 1998)
"A Master's Degree" by Margaret Hill McCarter is a novel written during the early 20th century. The story unfolds at Sunrise College in Kansas, focusing on the lives of several characters, particularly that of Professor Lloyd Fenneben, a driven college dean trying to balance his academic ideals with the demands of frontier life, and Victor Burleigh, a rough country boy eager to improve his station in life through education. Their intertwined paths set the stage for an exploration of ambition, rivalry, and personal growth against a backdrop of educational struggles and social dynamics in a budding Western society. At the start of the novel, we are introduced to the contrasting characters of Professor Vincent Burgess, an Eastern scholar, and Vic Burleigh, a country boy straight from the Kansas plains, as they enter Sunrise College on the same day. Their initial meeting is tinged with mutual skepticism, foreshadowing their evolving rivalry, particularly around Elinor Wream, the president's niece, who becomes a focal point of interest for both men. The narrative quickly explores Dean Fenneben's dedication to shaping his college as an institution of higher learning, while also delving into his personal reflections about the nature of education and the ideological clashes between Eastern academic traditions and the practical realities of the West. As the opening chapters unfold, themes of perseverance, character building, and the complexity of human connections become central to the story's development. (This is an automatically generated summary.)
Release date is 1998-06-01
Produced by Charles Keller, and David Widger
Keywords: Didactic fiction; College teachers -- Fiction